Oxygen Variability and Tropical Atlantic Circulation Cruise No. M130 August 28 - October 3, 2016 Mindelo (Cape Verde) - Recife (Brazil) ... - Dengler, Marcus (GEOMAR, 2017)
A physical - biogeochemical survey was carried out in the northeastern tropical Atlantic and in the western tropical South Atlantic. The main objective of the works in the oxygen minimum zone of the eastern tropical North Atlantic was to improve oxygen budget estimates. Additional objectives were to investigate the role of zooplankton for fluxes of particulate and dissolved organic matter and to advance quantitative understanding of nitrogen fixation in the tropical Atlantic. The main objective of the measurements program in the western tropical South Atlantic was to investigate the variability of transport and water mass properties of the western boundary circulation. A major component of the work program was the recovery of nine and the redeployment of eight moorings. The moorings positioned off Cape Verde, in the tropical northeastern Atlantic and at the western boundary off Brazil are collecting velocity, oxygen, temperature, and salinity time series since several years. All moorings were successfully ...